2017
DOI: 10.1055/s-0043-122385
|View full text |Cite|
|
Sign up to set email alerts
|

Artificial intelligence may help in predicting the need for additional surgery after endoscopic resection of T1 colorectal cancer

Abstract: Background and study aims Decisions concerning additional surgery after endoscopic resection of T1 colorectal cancer (CRC) are difficult because preoperative prediction of lymph node metastasis (LNM) is problematic. We investigated whether artificial intelligence can predict LNM presence, thus minimizing the need for additional surgery. Patients and methods Data on 690 consecutive patients with T1 CRCs that were surgically resected in 2001 – 2016 were retrospectively analyzed. We divided patients int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
109
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(110 citation statements)
references
References 27 publications
1
109
0
Order By: Relevance
“…Gastroenterologists made use of convolutional neural networks among other deep learning models in order to process images from endoscopy and ultrasound (32) and detect abnormal structures such as colonic polyps (33). Artificial neural networks have also been used to diagnose gastroesophageal reflux disease (34) and atrophic gastritis (35), as well as to predict outcomes in gastrointestinal bleeding (36), survival of esophageal cancer (37), inflammatory bowel disease (38), and metastasis in colorectal cancer (39) and esophageal squamous cell carcinoma (40).…”
Section: Gastroenterologymentioning
confidence: 99%
“…Gastroenterologists made use of convolutional neural networks among other deep learning models in order to process images from endoscopy and ultrasound (32) and detect abnormal structures such as colonic polyps (33). Artificial neural networks have also been used to diagnose gastroesophageal reflux disease (34) and atrophic gastritis (35), as well as to predict outcomes in gastrointestinal bleeding (36), survival of esophageal cancer (37), inflammatory bowel disease (38), and metastasis in colorectal cancer (39) and esophageal squamous cell carcinoma (40).…”
Section: Gastroenterologymentioning
confidence: 99%
“…With recent advances in endoscopic treatments, such as ESD, many T1 CRCs can be resected endoscopically with negative margin. Although endoscopic treatment is an attractive option for the patients, T1 CRCs show approximately 10% of LNM, which requires surgical colectomy with lymph node dissection to cure the cancer (13)(14)(15)(16)(17)(18)(19)(20). Therefore, it is important to reveal the risk factors for LNM in the patients with T1 CRCs, and we should decide whether additional surgery after endoscopic resection is needed according to the presence of risk factors for LNM.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, prospective studies still are needed because the role of morphology has not been confirmed in other settings. 11 In conclusion, we must admit that the convergence between the protective effect of the pedunculated morphology, on one side, and the much lower prevalence of histologic risk factors in pedunculated T1 CRCs, on the other, somewhat simplifies the incorporation of morphology in the clinical management of these lesions, further supporting the use of different management approaches between pedunculated and nonpedunculated T1 CRCs.…”
mentioning
confidence: 92%